Infectious diseases of neotropical primates - Oliveira, Ayisa Rodrigues; Santos, Renato Lima (Brazilian Journal of Veterinary Pathology, 2023)
Neotropical primates are represented by more than 200 species and subspecies distributed in five families. Considering that some of these species are considered endangered, disease investigation in these populations is critical for conservation strategies. Therefore, an increasing number of studies and publications on this topic became available in the past few years. This review deals with infectious diseases of neotropical primates, with focus on free-ranging animals, including those caused by bacterial, viral, protozoal, metazoan, or mycotic infectious organisms, with particular emphasis on gross and microscopic lesions associated with these diseases. In addition, a few relevant unpublished cases of infection by Staphylococcus spp., Streptococcus spp., E. coli and Pseudomonas spp. were included in this review.